INUNDATION ANALYSIS OF SOUTH JAKARTA JALAN TIONG AREA USING HEC-RAS - Mohammad Imamuddin; Rizki Priya Ramadan (International Journal of Civil Engineering and Infrastructure, 2023)
The Tiong Channel is located on Jalan Tiong Karet Kuningan, South Jakarta, geographically located between 6°13'06.5" South Latitude and 106°49'17.0" East Longitude. On Jalan Tiong often floods when the rainy season arrives. The flood was caused by several factors, one of which was the drainage channel that could not function properly. At several points in the water channel that will lead to the Krukut River there is a lot of plastic waste from residents which causes narrowing of the channel. The non-uniform channel dimensions are also the cause of flooding, there are several channel points that experience narrowing. From the above conditions, it is necessary to do an analysis of flood problems in the Tiong Karet Kuningan Canal area of South Jakarta to find out whether the Tiong Karet Kuningan Canal in South Jakarta can still accommodate water discharge based on rainfall in the last 10 years and whether the Tiong Karet Kuningan Canal in South Jakarta needs to be normalized. Based on the results of manual calculations and the HEC-RAS application, the Tiong Karet Kuningan Canal in South Jakarta cannot accommodate water discharge based on rainfall in the last 10 years of 12.61 m3/s. At point 0 – point 350 it is necessary to normalize by widening the channel to 2 m and increasing the depth/height of the channel to 2 m. and planning of sluice gates on the downstream of the canal.